2013
DOI: 10.1128/aem.02748-12
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous Mycobacteria, Fungi, and Opportunistic Pathogens in Unchlorinated Drinking Water in the Netherlands

Abstract: aThe multiplication of opportunistic pathogens in drinking water supplies might pose a threat to public health. In this study, distributed unchlorinated drinking water from eight treatment plants in the Netherlands was sampled and analyzed for fungi, nontuberculous mycobacteria (NTM), and several opportunistic pathogens by using selective quantitative PCR methods. Fungi and NTM were detected in all drinking water samples, whereas Legionella pneumophila, Pseudomonas aeruginosa, Stenotrophomonas maltophilia, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 56 publications
(69 reference statements)
2
66
2
Order By: Relevance
“…These results show that a low BFR, AOC, and ATP concentration in drinking water has limited impact on the NTM community composition in the drinking water distribution system. A previous study had shown van der Wielen et al that the AOC and/or BFR of the drinking water did not affect the 16S rRNA gene copy numbers of NTM in unchlorinated drinking water in the Netherlands (38). It can be concluded from our studies that both the NTM numbers and NTM community composition cannot be controlled by further reduction of the microbial activity, AOC concentration, and/or BFR in unchlorinated drinking water in the Netherlands.…”
Section: Discussioncontrasting
confidence: 37%
See 2 more Smart Citations
“…These results show that a low BFR, AOC, and ATP concentration in drinking water has limited impact on the NTM community composition in the drinking water distribution system. A previous study had shown van der Wielen et al that the AOC and/or BFR of the drinking water did not affect the 16S rRNA gene copy numbers of NTM in unchlorinated drinking water in the Netherlands (38). It can be concluded from our studies that both the NTM numbers and NTM community composition cannot be controlled by further reduction of the microbial activity, AOC concentration, and/or BFR in unchlorinated drinking water in the Netherlands.…”
Section: Discussioncontrasting
confidence: 37%
“…Consequently, the different NTM populations in winter and summer samples in the distributed drinking water of plant SW1 might indicate that NTM communities differ between the premise plumbing and distribution systems. A seasonal effect on the NTM numbers in distributed drinking water has been observed before (38,39), as has an effect of the premise plumbing system (25,38). Therefore, additional experiments are required to determine whether the NTM community in distributed drinking water is affected by the season and/or the premise plumbing system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the dosage of P. aeruginosa required to infect 50% of the tested mice hosts ranged from 5 x 10 3 till 2 x 10 4 cells [41], the amount of P. aeruginosa in the UF permeate was lower than the required infectious dosage and should not impose any significant risk to the public health. Coincidentally, the regA gene of P. aeruginosa was also occasionally detected in drinking water in Netherlands at up to 4.4 x 10 3 copies/L [42], suggesting that P. aeruginosa may be ubiquitous in oligotrophic drinking water supplies including those potable waters generated from a desalination plant. Finally, despite an increased abundance of genus Pseudomonas after CEB cleaning, the black coloration of bacterial cultures was not observed for these chemically cleaned UF membranes ( Figure 7B).…”
Section: Discussionmentioning
confidence: 99%
“…In untreated water, NTM can even parasitize amoebae (4,5). Even when the water supply is treated, NTM persist, and a very recent study in Holland (6) found NTM in samples of drinking water from eight separate treatment plants.…”
Section: Ecology and Epidemiologymentioning
confidence: 99%